Evaluation of dabigatran, rivaroxaban and apixaban target-specific assays in a multicenter French study. Issue 158 (October 2017) - ; Abecassis, Line; Aillaud, Marie-Françoise; Ajzenberg, Nadine; Alhenc-Gelas, Martine; Flory, Anny Appert; Bauters, Anne; Biron, Christine; Berruyer, Micheline; Jouvan, Florence Blanc; Brionne-François, Marie; d'Audigier, Clément; et al.
Abstract: Dabigatran etexilate, rivaroxaban and apixaban (DOACs) are widely used and measurement of their concentration is desirable in certain clinical situations. Target-specific assays are available but limited information exists on their performance especially in their ability to accurately measure low and high concentrations. Aims: To define, in a multicenter study, the precision and accuracy of DOAC measurements in daily practice. Methods: 15 plasma samples (kindly provided by Hyphen-Biomed) spiked with 5 blinded concentrations of dabigatran, rivaroxaban or apixaban (targeted 0–40–100–250–500 ng/mL, actual concentrations measured by HPLC-MS/MS), were sent to 30 haemostasis laboratories. DOAC concentration, PT and aPTT were measured once in each sample using local reagents. Interlaboratory precision was determined by its coefficient of variation (CV) and accuracy by its bias. Results: 464 DOAC measurements were performed in the 30 laboratories using 4 dabigatran and 5 rivaroxaban/apixaban calibrated assays on 3 analysers. Inter-laboratory CVs were below 18% for concentrations ≥ 100 ng/mL, and higher for concentrations ~ 40 ng/mL; biases were below 8% for all drugs and concentrations. In DOAC-free samples, concentrations were all below the lower limit of quantification except for one value (dabigatran: 35 ng/mL). Depending on the concentrations, significant differences were found between reagents in rivaroxaban and apixaban concentration values. PT and aPTT ratios displayed a low sensitivity to apixaban. Conclusion: Our results suggest that calibrated DOAC assays allow the reliable measurement of a wide range of drug concentrations, even though improvement of their performances is necessary, especially for measuring low concentrations. Highlights: Information on the performances of direct oral anticoagulants (DOAC) assays are required. A wide range of DOAC concentrations were tested in a multicenter study (30 laboratories). Good accuracy and acceptable precision of DOAC commercial assays were found. Improvements are necessary for measuring low DOAC concentrations. PT or aPTT are unable to detect low concentrations of rivaroxaban and dabigatran and "on-therapy" concentrations of apixaban.